2016
DOI: 10.1016/j.canlet.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Ad5/35E1aPSESE4: A novel approach to marking circulating prostate tumor cells with a replication competent adenovirus controlled by PSA/PSMA transcription regulatory elements

Abstract: Circulating tumor cells serve as useful biomarkers with which to identify disease status associated with survival, metastasis and drug sensitivity. Here, we established a novel application for detecting PSA/PSMA-positive prostate cancer cells circulating in peripheral blood employing an adenovirus called Ad5/35E1aPSESE4. Ad5/35E1aPSESE4 utilized PSES, a chimeric enhancer derived from PSA/PSMA promoters that is highly active with and without androgen. A fluorescence signal mediated by GFP expression upon Ad5/35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…FCER1G inhibits the expression of certain Alzheimer's disease susceptibility genes by participating in Herpes simplex (HSV-1) escape strategy [9]. Interestingly, the abundant expression of FCER1G was found in the circulating tumor cells of a prostate cancer patient who was sensitive to docetaxel chemotherapeutic reagent [32]. In the PPI network, many important genes that were associated with MM had been screened.…”
Section: Discussionmentioning
confidence: 99%
“…FCER1G inhibits the expression of certain Alzheimer's disease susceptibility genes by participating in Herpes simplex (HSV-1) escape strategy [9]. Interestingly, the abundant expression of FCER1G was found in the circulating tumor cells of a prostate cancer patient who was sensitive to docetaxel chemotherapeutic reagent [32]. In the PPI network, many important genes that were associated with MM had been screened.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the identification of novel markers specifically expressed on CTCs that are not down-regulated during EMT may increase the potential for utilizing CTCs in the clinical setting. To overcome the limitations associated with the high level of sensitivity required to isolate CTCs, we developed a novel technology using a replicationcompetent adenovirus, Ad5/5E1aPSESE4, to label PSA/PSMA(+) cells (7). Interestingly, this adenovirusbased diagnostic tool provided similar results as conventional image-guided or PSA-based predictions of disease progression in most patients, although several patients with local tumors harbored too few CTCs in the blood to facilitate this type of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For the separation of peripheral blood mononuclear cells (PBMCs) from whole blood, 5 ml of whole blood in a K2 EDTA tube was added to a 50 ml conical tube containing 4 ml of Ficoll-Paque PLUS (GE Healthcare Life Science, Pittsburg, PA, USA) and was gently mixed with PBS to reach a total volume of 10 ml. The PBMC sample was prepared in a 12-well plate as described (7). Then, PBMCs were infected with 0.01 multiplicity of infection (MOI) of Ad5/35E1aPSESE4 and determined whether to contain CTCs mediating green fluorescent protein (GFP) expression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the cytotoxic activity demonstrated that Ad5/35PSES.mRFP/ttk killed LNCaP and CWR22rv cells more effectively. In addition, the chimeric oncolytic adenovirus Ad5/35E1aPSESE4 also effectively killed PSA/PSMA-positive PCa cells in the peripheral circulation ( 112 ).…”
Section: Modification Of Adenovirus Capsid Proteins To Construct An Amentioning
confidence: 99%